The effectiveness of MAJAICO training in promoting Japanese work culture among PROTON employees at PTMSB / Nurul Husna Ramlie - Ramlie, Nurul Husna (2011)
Employee’s work performance plays a vital role in every organization either to give positive or negative influence towards productivity depends on how the employees perform and the levels of competencies skills have in accomplishing the work task. The latest knowledge, skills, attitudes, commitments and performances are needed to take into consideration by organization in order to get higher productivity and to give a good impact to organization’s profit. In order to get a better employee’s work performance, MAJAICO training can be the suitable solution which can be taken by the organization. Therefore, this case study attempts to identify the effectiveness of MAJAICO training centre in promoting Japanese work culture. Five dimensions have been chosen as the focus of this study which is knowledge, skills, attitudes, commitments and performances. MAJAICO training introduces the Kaizen, 5’S and activities mainly through the implementation of the Lean Production System (LPS) which increases production efficiency, thereby reducing waste and cost. The activities will be conducted by the Japanese experts’ in this field. The result of this study indicates MAJAICO training provides the effective impact to the PROTON employees. Besides that, MAJAICO training program also proves that the Japanese work culture can be suitable and effective to the PROTON employees’ in PTMSB regarding to their work performance and development.